Selected microwave irradiation effectively inactivates airborne avian influenza A(H5N1) virus - Pietro Bia; Margherita Losardo; Antonio Manna; Silvio Brusaferro; Gaetano P. Privitera; Alberto Sangiovanni Vincentelli (Scientific Reports)
Abstract The highly pathogenic avian influenza A(H5N1) virus threatens animal and human health globally. Innovative strategies are crucial for mitigating risks associated with airborne transmission and preventing outbreaks. In this study, we sought to investigate the efficacy of microwave inactivation against aerosolized A(H5N1) virus by identifying the optimal frequency band for a 10-min exposure and evaluating the impact of varying exposure times on virus inactivation. A(H5N1) was aerosolized and exposed to various microwave frequencies ranging from 8 to 16 GHz for a duration of 10 min. Viral titers were quantified using TCID50, and inactivation was assessed by comparing irradiated samples to controls. The 11–13 GHz band yielded the highest inactivation, with an average 89% mean reduction in A(H5N1) titer, particularly within the 11–12 GHz range, which exhibited peak efficacy. Based on the overall results, the optimal frequency band (8–12 GHz) was further tested with exposure durations of 1, 3, and 5 min. Inactivation was time-dependent, with a 5-minute exposure resulting in a 94% mean reduction, compared to 58% and 48% for 3- and 1-minute exposures, respectively. We conclude that optimized microwave emitters in high-risk environments like poultry farms and veterinary clinics could offer a novel, non-chemical approach to mitigating avian influenza spread and outbreaks.